Strategy for Empowering Indigenous Papuan Fishermen in the Implementation of Papua's Special Autonomy Law - Hermanu Iriawan; Edyanto Edyanto (Universitas Padjadjaran, 2023)
This research was conducted at the Marine and Fisheries Service of Biak Numfor Regency. This research uses qualitative research methods with a case study approach. The techniques used in collecting this research data through observation and interviews. To obtain truly valid data, the data is tested by triangulation. The results showed that the empowerment of indigenous Papuan fishing communities in the implementation of the Papua Special Autonomy Law carried out by the government through the Marine and Fisheries Service of Biak Numfor district, including; provision of training on catch processing skills, provision of home industry facilities and infrastructure, and formation of indigenous Papuan fishermen groups. conclusion is the government's efforts to encourage active participation of indigenous Papuan fishing communities in the process of developing the fisheries sector, so as to strengthen relations between the government and the community and increase public trust and support for development efforts in their own regions.